A socio-legal study on a purchaser's interest under housing developers (control and licensing) act 1966 and housing developers (control and licensing) regulations 1982 / Noor Hadi Sallehon - Sallehon, Noor Hadi (Faculty of Law, 1982)
When peopl e thi nk of buyi ng a house, the fi rst category of sell ers to come to their mind is the housing developers. In governing and contro11 i ng hous i ng development in Malays i a, spec ifi c 1egi slat ion passed by the parliament is The Housing Devel.opers (Control and Licensing) Act 1966.This Act was first introduced in 1966 and came into force on the 29th August 1969. The Revi sed Act came into force on 16th August 1973 with its ori gi nal form still preserved. In addit ion with the power stipulated in section 24 ·of the Act, The Minister of Housing and Local Government, has introduced various subsidiary legislations. The present subsidiary legislation promulgated by The Minister is Housing Developers (Control and Licensing) Regulations 1982 whi ch came into force on June 1st, 1982 and were gazetted on April 29th. By virtue of Regulation 16 of the said regulations, The Housing Developers (Control and Licensing) Rules 19703 are hereby repea 1ed. Apparently when the 1982 Regul at ions were introduced, there were some mixed reactions from the members of The Legal Profession engaged in conveyancing practice, Housing Developers and Consumers' Associations.